1998
DOI: 10.1097/00000539-199802000-00034
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Influence of Pulmonary Vagal Afferents on Respiratory Distress Induced by Airway Occlusion in Halothane-Anesthetized Cats

Abstract: In anesthetized cats, we found that lung expansion reduces the tolerable limit to airway occlusion and vagotomy decreased minimum alveolar anesthetic concentration for airway occlusion, which suggests that pulmonary vagal afferents play an important role in relief of respiratory distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In keeping with these observations, Nehashi et al ( 2001 ) reported that nebulized furosemide inhibited respiratory distress induced by airway occlusion in anesthetized cats. Sakurai et al ( 1998 ) similarly reported that lung expansion inhibited respiratory distress induced by airway occlusion in a dose-related manner and that bilateral vagotomy totally abolished this effect, presumably via loss of sensory feedback from PSRs. On the basis of these observations and the purported role of PSRs in the neuromodulation of breathlessness in humans (Manning et al, 1992 ; Flume et al, 1996 ; Vovk and Binks, 2007 ), it has been proposed that nebulized furosemide alleviates breathlessness by altering pulmonary vagal afferent activity from PSRs, presumably mimicking greater tidal volume (V T ) expansion (Nishino et al, 2000 ; Sudo et al, 2000 ; Nehashi et al, 2001 ; Moosavi et al, 2007 ; Nishino, 2009 ).…”
Section: Introductionmentioning
confidence: 97%
“…In keeping with these observations, Nehashi et al ( 2001 ) reported that nebulized furosemide inhibited respiratory distress induced by airway occlusion in anesthetized cats. Sakurai et al ( 1998 ) similarly reported that lung expansion inhibited respiratory distress induced by airway occlusion in a dose-related manner and that bilateral vagotomy totally abolished this effect, presumably via loss of sensory feedback from PSRs. On the basis of these observations and the purported role of PSRs in the neuromodulation of breathlessness in humans (Manning et al, 1992 ; Flume et al, 1996 ; Vovk and Binks, 2007 ), it has been proposed that nebulized furosemide alleviates breathlessness by altering pulmonary vagal afferent activity from PSRs, presumably mimicking greater tidal volume (V T ) expansion (Nishino et al, 2000 ; Sudo et al, 2000 ; Nehashi et al, 2001 ; Moosavi et al, 2007 ; Nishino, 2009 ).…”
Section: Introductionmentioning
confidence: 97%